Practical Considerations in Particle and Object Tracking and Analysis. Issue 1 (3rd May 2019) - Aaron, Jesse; Wait, Eric; DeSantis, Michael; Chew, Teng‐Leong
Abstract: The rapid advancement of live‐cell imaging technologies has enabled biologists to generate high‐dimensional data to follow biological movement at the microscopic level. Yet, the "perceived" ease of use of modern microscopes has led to challenges whereby sub‐optimal data are commonly generated that cannot support quantitative tracking and analysis as a result of various ill‐advised decisions made during image acquisition. Even optimally acquired images often require further optimization through digital processing before they can be analyzed. In writing this article, we presume our target audience to be biologists with a foundational understanding of digital image acquisition and processing, who are seeking to understand the essential steps for particle/object tracking experiments. It is with this targeted readership in mind that we review the basic principles of image‐processing techniques as well as analysis strategies commonly used for tracking experiments. We conclude this technical survey with a discussion of how movement behavior can be mathematically modeled and described. © 2019 by John Wiley & Sons, Inc.